A Feasibility Study Comparing Platelet-Rich Plasma Injection With Saline for the Treatment of Plantar Fasciitis Using a Prospective, Randomized Trial Design. Issue 2 (April 2019) - Johnson-Lynn, Sarah; Cooney, Alan; Ferguson, Diarmaid; Bunn, Deborah; Gray, William; Coorsh, Jonathan; Kakwani, Rajesh; Townshend, David
Platelet-rich plasma (PRP) has been advocated for treatment of plantar fasciitis but there are few good-quality clinical trials to support its use. We conducted a feasibility study of PRP versus saline for treatment of plantar fasciitis. Patients with 6 months or more of magnetic resonance imaging–proven plantar fasciitis, who had failed conservative treatment were invited to participate in the study. Patients were block randomized to either PRP or an equivalent volume of saline. The techniques used for injection and rehabilitation were standardized for both groups. The patient and assessor were blinded. Visual analogue scale (VAS) for pain and painDETECT score were recorded preoperatively and at 6 months follow-up. From 35 patients approached, 28 (19 female, mean age 50 years) were recruited, with 14 randomized to each arm. At 6 months, 8 patients (28.6%) were lost to follow-up. There was a significant change in VAS score from baseline to follow-up in both intervention (mean change 37.2, P = .008) and control (mean change 42.2, P = .003) groups. There was no correlation between preoperative painDETECT score and change in VAS. Recruitment and loss to follow-up rates were relatively high. Both treatments resulted in a similar, significant, improvement in symptoms. Levels of Evidence: Level II